Intervensi Berbasis Teori Growth Mindset Carol Deck Pada Remaja Komunitas Pramuka - Annisa Eka Cholysia; Fauzi Triastianto; Jihan Nur Sesha; Khofifah Salsabilah Tasya; Yola Chairunisa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This community service initiative aimed to assess the effectiveness of a psychoeducational intervention based on Carol Dweck’s growth mindset theory among adolescents participating in Scout activities at MTs Terpadu Attaqwa 04. The intervention employed an experiential learning approach, incorporating material presentation, discussions, educational games, reflection, and case studies. Seven Scout members participated in the study. Evaluation was conducted using pre-tests and post-tests to measure changes in attitudes and knowledge. The results showed an increase in the average attitude score from 45 to 46 and a rise in the knowledge score from 8 to 10 following the intervention. Throughout the activities, participants demonstrated active engagement, the confidence to express their opinions, and improved teamwork. These findings indicate that growth mindset-based psychoeducation can help adolescents understand that abilities can be developed through effort, practice, and learning experiences, thereby potentially fostering more resilient, confident, and adaptive character traits.